The postbiotic of hawthorn-probiotic ameliorating constipation caused by loperamide in elderly mice by regulating intestinal microecology - Wei, Yu; Huang, Na; Ye, Xinyu; Liu, Meng; Wei, Meilian; Huang, Yali (Frontiers in Nutrition, 2023)
Background: Constipation is common gastrointestinal disorder with high prevalence and recurrence, making people suffering. However, the treatment for constipation remains ineffectual. We aimed to the study the effects and mechanisms of postbiotic of hawthorn-probiotic on loperamide modelled old KM mice. (2) Methods: Constipated mice were grouped and treated with 10% lactulose (Y), hawthorn group (S), probiotic group (F) and postbiotic of hawthorn-probiotic (FS). Fecal changes were observed. AQP3 and Enac-γ were measured by RT-qPCR and Western blotting, intestinal barrier by H&E and immunofluorescence staining, cell proliferation and apoptosis by CCK8 and flow cytometry. Gut microbiota was further determined by 16s rRNA sequence of feces. (3) Results: Postbiotic of hawthorn-probiotic improved intestinal movement and pathomorphology, elevated AQP3, Enac-γ and mucin-2 expression, accompanied by decreased serum TNF-α and cell apoptosis, but increased proliferation. Furthermore, it modified the gut microbiota of constipated mice, featured by upregulation of Lactobacillaceae. (4) Conclusions: Postbiotic of Hawthorn-Probiotic relieved constipation by combined effects of regulating intestinal water and sodium metabolism, maintain intestinal barrier and gut microflora.